Association of Picky Eating with Growth, Nutritional Status, Development, Physical Activity, and Health in Preschool Children - Hsun-Chin Chao (Frontiers Media S.A., 2018)
BackgroundThis study aimed to assess the prevalence of picky eating among preschool children and to evaluate the association between eating behavior and growth, physical activity, development, and health status.MethodsA structured questionnaire was used to conduct a cross-sectional descriptive study of 300 primary caregivers of children aged 2-4 years in Taiwan. Data collected included: demographics, food preferences, eating behavior, body weight, and height, development, physical activity, and records of medical illness. Data from children defined as picky or non-picky eaters based on parental' questionnaire responses were analyzed and compared using standard statistical tests.ResultsThe mean age of the children was 2.95 years; 162 (54%) were picky eaters. Compared with non-picky eaters, z-score of weight-for-age, height-for-age, and body mass index (BMI)-for-age in picky eaters was 0.91, 0.73, and 0.44 SD lower, respectively. There were significant differences of rates in the weight-for-age, height-for-age, and BMI-for-age percentiles <15, between picky and non-picky eaters (P = 0.04, 0.023, and 0.005, respectively). Fear of unfamiliar places, poor physical activity, constipation, and high frequency (>2 times in the past 3 months) of medical illness were significantly higher in picky eaters (P = 0.01, 0.001, 0.044, and <0.001, respectively).ConclusionThe prevalence of picky eaters in preschool children was high, resulting in significant detrimental impacts on growth, nutritional status, development, physical activity, and health status.